Esterilizaciones forzadas, narrativa participativa y contramemoria digital en el Perú - Brown, Matthew (2018)
This article aims to prompt reflection on the ways in which digital research methods can support or undermine participatory research. Building on our experiences of working on the Quipu Project (quipu-project.com), an interactive, multimedia documentary on unconsented sterilization in Peru, it explores the ways in which digital technologies can enable participatory knowledge production across geographic, social and linguistic divides. It also considers the new forms of engagement between knowledge-producers and audiences that digital methods can encourage. Digital technologies can, we contend, help build new spaces for, and modes of engagement with, participatory research, even in contexts such as the Peruvian Andes where digital technologies are not well established or commonly used. Doing so, we argue, entails responding sensitively to the social, linguistic and digital inequalities that shape specific research contexts, and centering the human relationships that are easily sacrificed at the altar of technological innovation.